Povezanost individualnih značilnosti in dejavnikov konteksta z naravoslovnimi dosežki slovenskih dijakov na PISI 2006 - Zupančič, Maja (Šolsko polje, 2009)
In this paper we analyze data on science literacy PISA 2006 which were collected with 15-year-old Slovene secondary school students. Differences in students' scores across domains of general science performance, science competencies, and attitudes towards science were explored among four secondary educational programs, among schools within the programs, and at the level of students. Considering three-level models, the differences in science performance and competencies were mainly explained by the differences among programs and by students' individual differences, whereas the contribution of differences among schools within the same program was smaller. On average, students of vocational secondary schools scored the lowest and general high school students obtained the highest scores. Individual differences among students account for most of the differences in students' attitudes towards science, while contributions of differences among the programs and among the schools are negligible. Considering two-level models (at the school-program level and at the level of students), the model which includes predictors, i.e. individual characteristics of students and context (home, school) variables, explains considerably larger proportions of variance across the domains of science literacy than the null model. All of the predictors jointly account for somewhat more than a half of variance (at the school-program level and at the level of students) in general science performance and in science competencies. The contribution of predictors is smaller with regard to students' attitudes towards science. Students' motivation to learn science, perceived self-efficacy, and teaching science were consistently demonstrated to be significant single predictors in each of the domains of science literacy.
Keywords: dijaki; mednarodne raziskave; naravoslovje; PISA; Slovenija; vzgoja in izobraževanje; znanje